ISLAM DAN KOMUNISME: ANALISIS PEMIKIRAN ISLAM DAN EPISTEMOLOGI PERGERAKAN HAJI MISBACH - Yusuf, Sulaiman; Arqam, Abil (Pustaka Peradaban, 2024)
Islam and Communism are often perceived as two irreconcilable ideologies. However, these two ideologies share common ground in their struggle for the rights and justice of the common people against the oppression of capitalism. Haji Misbach, an Islamic movement figure and preacher, sought to connect Islam with communism. He led a movement based on both ideologies with the aim of fighting for the rights of indigenous people that were taken away by the government and capitalists. This movement focused on opposing capitalism and colonialism, and championing the rights of the oppressed working class and common people. Haji Misbach utilized writing and the mass media to influence the working class and advocate for their rights. The teachings of Islam and communism share commonalities in opposing oppression and violence, thus Haji Misbach attempted to juxtapose Islamic teachings with communism. This movement emboldened the indigenous people to resist oppression and influenced Misbach's thinking regarding the unification of Islamic teachings with communism, which later became known as Islamic communism. Islam dan Komunisme seringkali dianggap sebagai dua ideologi yang tak dapat bersatu. Padahal dua ideologi ini memiliki kesamaan dalam memperjuangkan hak dan keadilan bagi rakyat kecil dari penindasan yang dilakukan oleh kapitalisme. Haji Misbach adalah seorang tokoh pergerakan Islam dan mubaligh yang berupaya mempertautkan Islam dengan komunisme. Ia memimpin gerakan berbasis kedua ideologi ini dengan tujuan memperjuangkan hak-hak rakyat pribumi yang dirampas oleh pemerintah dan para pemilik modal. Gerakan ini berfokus pada penentangan kapitalisme dan kolonialisme serta memperjuangkan hak-hak kaum buruh dan rakyat kecil yang tertindas. Haji Misbach menggunakan tulisan dan media massa untuk mempengaruhi kaum buruh dan memperjuangkan hak-hak mereka. Ajaran Islam dan komunisme memiliki kesamaan dalam menentang penindasan dan kekerasan, sehingga Haji Misbach mencoba menyandingkan ajaran Islam dengan komunisme. Gerakan ini memberikan keberanian bagi kaum bumiputera untuk melawan penindasan dan mempengaruhi pemikiran Misbach terkait penyatuan ajaran Islam dengan komunisme, yang kemudian dikenal dengan istilah komunisme Islam.